ANALISIS EFEKTIVITAS DAN FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP REALISASI PEMBIAYAAN SEKTOR UMKM DI PERBANKAN SYARIAH - Rinna Ramadhan Ain Fitriah (Nusantara Interdisciplinary Journal of Education Studies and Society (NIJESS), 2024)
This research is motivated by the importance of financing the MSME sector based on sharia principles to overcome the problem of limited MSME business capital and avoid the element of usury. The MSME Financing Program based on sharia principles has been implemented by Islamic Financial Institutions, both banks and non-banks. MSME financing data found by PT BPD Kaltim Kaltara Syariah shows the amount of financing in the MSME sector is still smaller than financing in other sectors, thus questioning the effectiveness of financing in this sector. This study aims to determine the level of effectiveness of financing in the MSME sector and the factors that have a significant effect on the realization of MSME financing at PT BPD Kaltim Kaltara Syariah Samarinda Branch. This study focuses on two analyzes, namely the analysis of the effectiveness of financing the MSME sector and the analysis of the factors that influence the realization of MSME financing at PT BPD Kaltim Kaltara Syariah Samarinda Branch. To analyze the effectiveness of MSME financing, the method used is a mixed qualitative-quantitative research method (mixed methods concurrent triangulation) which analyzes the effectiveness from two sides, namely from the internal side (qualitative data on bank criteria) and from the external side (quantitative data on perceptions of MSME customers). Meanwhile, to analyze the factors that influence MSME financing using multiple linear regression analysis method, the estimated independent variables are the age of the customer, the customer's education level, the length of the customer's business, the net profit of the business per month, the type of business, the composition of business capital, the value of collateral, and types of financing contracts. Multiple linear regression analysis was tested with the SPSS 23.0 statistical tool. The results of the analysis show that the MSME financing of PT BPD Kaltim Kaltara Syariah Samarinda Branch has been running effectively, except in the case of closing the MSME sector financing distribution target due to declining regional economic conditions. While the results of the analysis of the factors that influence MSME financing, based on the results of the t-test, show that partially there are two factors that have a significant effect on the realization of MSME financing at a significant level of 5%, namely the customer's net profit per month with a significant level of 0.013 and the value of financing funds. with a significant level of 0.000.